Financial Sector Assessment Program : Review, Lessons, and Issues Going Forward. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This paper reports on developments in the Financial Sector Assessment Program (FSAP) since the last Board review of the FSAP in spring 2003 and discusses staff views of the programs evolution.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet